The New Territory : Ralph Ellison and the Twenty-First Century - Morel, Lucas E., 1964-; Conner, Marc C., 1965- (Book collections on Project MUSE., 2016)
"Ralph Ellison once said, "We're only a partially achieved nation." In The New Territory, scholars show how clearly Ellison foresaw and articulated both the challenges and the possibilities of America in the twenty-first century. Indeed, Ellison in these new essays appears more and more to be a cultural prophet of twenty-first century America. As literary scholar Ross Posnock states, "If in our global, transnational age the renewed promise of cosmopolitan democracy has emerged as an animating ideal of popular political, and academic culture, this is a way of saying that we are only now beginning to catch up with Ralph Waldo Ellison." In this collection, the editors offer fourteen original essays that seek to examine and re-examine Ellison's life and work in the context of its meanings for our own age, the early twenty-first century, the age of Obama, a period that is seemingly post-racial and yet all too acutely racial. Following a careful introduction that situates Ellison's writings in the context of new approaches and interest in his work, the book offers new essays examining Ellison's 1952 masterpiece, Invisible Man. It then turns to his vast, unfinished second novel, Three Days Before the Shooting... , with detailed readings of that powerful and elusive narrative. These essays are the first sustained treatments of that posthumous work. The New Territory concludes with five chapters that discuss Ellison's political, cultural, and historical significance, probing how he speaks to the contemporary moment and beyond" -- From the publisher.